Design of a 24 GHz pattern reconfigurable slotted Yagi-Uda antenna on substrate integrated waveguide - Limpiti, T.; Krairiksh, M. (My University, 2013)
This paper presents the design of a linearly polarized pattern reconfigurable antenna whose configuration employs a single feed and a low profile cavity backed slot antenna. The grounded coplanar waveguide feed is adopted to excite the slotted Yagi-Uda structure which is constructed on the substrate integrated waveguide (SIW). The whole antenna is thus completely constructed on a single layer of a printed circuit board (PCB) substrate. The concept of pattern reconfiguration is based on switching function between the director- and the reflector-parasitic slots of PIN diodes. This antenna is designed to operate at the frequency of 24 GHz that there are various applications, e.g., Doppler sensor in automotive and industrial applications, security applications, and communication applications. The simulation results show good matching and interesting performance in reconfiguring the radiation patterns. © 2013 IEEE.
Keywords: Pattern reconfigurable; PIN diode; slot antenna; substrate integrated waveguide; Yagi-Uda antenna